APPROPRIATIONS OF POLICIES RELATED TO L2 ACADEMIC WRITING PRACTICES IN AN INDONESIAN EFL TEACHER EDUCATION PROGRAM - Joseph Ernest Mambu (Universitas Katolik Indonesia Atma Jaya, 2013)
The current study investigates state and local polices that regulateacademic writing and how they are appropriated in an English-as-a-Foreign-Language (EFL) teacher education program in Indonesia.The significance of the current study lies in its affirmation to thenotion that policy appropriations are multi-layered. That is,government policies may or may not be translated into local de jureand de facto regulations, and in turn these local policies evolve asthey are used and negotiated among colleagues and/or withstudents. In an attempt to understand the layers of appropriations,interviews with four local instructors were conducted. This researchwill pave the way for further praxes to provide quality academicwritinginstructions, in the light of, or regardless of, the stateregulations.Keywords: policy appropriation, second language academicwriting, publication, agency